El léxico de la pandemia: un estudio de disponibilidad léxica con estudiantes de la Universidad de Salamanca - Delgado-Olmos, Alicia; Tellez-Perez, Clara; Ugueto Colina, Marluis Melissa (Rassegna Iberistica, 2023)
The aim of this study is to determine to what extent the pandemic might have influenced lexical retrieval in relation to everyday centers of interest. In order to achieve this, five centers of interest have been selected from Panhispanic Project of Lexical Availability (PPHLD). Additionally, the new centers Pandemia and Coronavirus have been added in two separate experiments. Our data suggest that the pandemic might be connected to changes in the lexical availability and the position of certain terms on the lexical availability lists, as well as to the inclusion of new words.